1980
DOI: 10.1103/physrevlett.44.1348
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Metallic Behavior of Thin Bismuth Whiskers

Abstract: The electrical resistance of Bi and Bi-6 at.% Sb whiskers has been measured. Sample diameters were as low as 140 nm, lengths as large as 1.5 mm, and residual resistances as high as 165 k£2. Down to temperatures of 0.4 K, metallic behavior persists; the resistance R decreases with decreasing temperature T in contrast to other systems in which electron localization is invoked to explain negative dR/dT's.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Concept of ' maximum metallic resistivity '. Minami and Hori (1970) Dolan and Osheroff (1979) Habermeier (1980) Giordano (1980) Whitelaw and McLaughlin (1981) Thouless (1977) Giordano et al ( ) Overcash et al (1980 Bernasconi and Schneider (1981) Czycholl et al (1981) (b) Density of electronic states and band structure in one-dimension. Eisenschitz and Dean (1957) Beeby and Edwards (1963) Jones (1969) Mikhailov and Kolesnikov (1971) Cottey (1971) Roy (1972) Rice (1972) Gogolin (1979) Ford (1959) Zittartz and Langer (1966) Gubernatis and Taylor (1971) Roy and Bhattacharya (1971) Thouless (1971) Papatriantafillou (1972) Sadovskii (1979) (c) Blair (1967) Gazaryan (1969) Penchina andMitchell (1972) Gogolin et al (1975) (d) Green function methods and electronic states.…”
Section: Related Subjectsmentioning
confidence: 97%
See 1 more Smart Citation
“…Concept of ' maximum metallic resistivity '. Minami and Hori (1970) Dolan and Osheroff (1979) Habermeier (1980) Giordano (1980) Whitelaw and McLaughlin (1981) Thouless (1977) Giordano et al ( ) Overcash et al (1980 Bernasconi and Schneider (1981) Czycholl et al (1981) (b) Density of electronic states and band structure in one-dimension. Eisenschitz and Dean (1957) Beeby and Edwards (1963) Jones (1969) Mikhailov and Kolesnikov (1971) Cottey (1971) Roy (1972) Rice (1972) Gogolin (1979) Ford (1959) Zittartz and Langer (1966) Gubernatis and Taylor (1971) Roy and Bhattacharya (1971) Thouless (1971) Papatriantafillou (1972) Sadovskii (1979) (c) Blair (1967) Gazaryan (1969) Penchina andMitchell (1972) Gogolin et al (1975) (d) Green function methods and electronic states.…”
Section: Related Subjectsmentioning
confidence: 97%
“…Eisenschitz and Dean (1957) Beeby and Edwards (1963) Jones (1969) Mikhailov and Kolesnikov (1971) Cottey (1971) Roy (1972) Rice (1972) Gogolin (1979) Ford (1959) Zittartz and Langer (1966) Gubernatis and Taylor (1971) Roy and Bhattacharya (1971) Thouless (1971) Papatriantafillou (1972) Sadovskii (1979) (c) Blair (1967) Gazaryan (1969) Penchina andMitchell (1972) Gogolin et al (1975) (d) Green function methods and electronic states. Ziman (1966) Pant andJoshi (1969) Foo and Ausloos (1972) Cyrot-Lackmann and Cyrot (1972) Transmission, conductivity and mean-free-path in one-dimension.…”
Section: Related Subjectsmentioning
confidence: 98%
“…It has been known for a long time that rhombohedral bulk Bi at ambient pressure is a semimetal down to at least 50 mK. Recent studies on this “old” material have uncovered a number of new phenomena, such as a quasi-one-dimensional (1D) topological metallic state at the (114) surface of a Bi crystal with a Fermi contour consisting of two closely separated, parallel lines of opposite spin direction, which resembles the 1D edge state in the quantum spin Hall effect (QSHE) . Metallic surface states are a prerequisite for the formation of a topological insulator , and have been found in bulk Bi 1– x Sb x with x = 0.07–0.22 .…”
mentioning
confidence: 99%
“…Because of its unusually rich electronic properties, Bi has long been the subject of experimental and theoretical studies. [1][2][3][4][5][6][7][8][9][10][11] At high pressure, however, Bi is superconducting at low temperatures due to the formation of high-pressure metallic polymorphs, namely, monoclinic Bi-II at 2.55 GPa, 12,13 a complex tetragonal Bi-III at 2.7 GPa, 12,[14][15][16] and a bodycentered cubic (bcc) Bi-V at 7.7 GPa. 12,16,17 The transition temperatures of these polymorphic phases are respectively 3.9, 18,19 7.2, [18][19][20] and 8.3 K. 20,21 It was found that these highpressure phases could be preserved in a metastable state by subjecting the bulk crystal to compression cycles at room temperature and releasing the pressure at helium tempera-tures.…”
mentioning
confidence: 99%